INTEGRITY OF VARIOUS ASPECTS OF SUSTAINABILITY - Maksims Kaimovs; Andrejs Skarupins (Izdevnieciba "Baltija Publishing", 2024)
In an era of rapid scientific and technological progress, the concept of sustainable development has become an important framework for addressing the multifaceted problems of resource scarcity, environmental degradation and social inequality. This article provides a comprehensive analysis of the evolution, principles and practical application of the concept of sustainable development, emphasising the interconnectedness of its three main dimensions: environmental, economic and social. The paper explores the integrity of the concept of sustainable development in different dimensions. The goal of the study is to provide a comprehensive analysis of the evolution, principles and practical application of the concept of sustainable development, emphasising the interconnectedness of environmental, social and economic aspects and their impact on sustainable development. The concept of sustainable development has evolved from early forestry practices to a broader encompassing of environmental, social and economic aspects. The concept gained prominence in the 20th century with the Club of Rome report and the Rio Earth Summit, leading to the widespread adoption of sustainable development as a guiding principle for global development. Central to sustainable development is the idea of meeting the needs of the present without compromising the ability of future generations to meet their own needs. The article identifies three traditional components of sustainable development: environmental, social and economic, and explores their interrelationship. Environmental sustainability focuses on the responsible use of natural resources and pollution management. Economic sustainability emphasises the importance of long-term economic stability and growth, while social sustainability addresses issues of equality, social justice, well-being and quality of life. The intersection of these pillars shows how integrated approaches can contribute to a resilient, equitable and livable environment. The publication highlights the role of sustainable development goals and standards in various areas. By harmonising environmental, economic and social goals, sustainable development offers a pathway to a resilient and prosperous global society. This holistic approach is essential to ensure the well-being of present and future generations in an increasingly interconnected world. The article emphasises the need for coordinated efforts at the local, national and global levels.